Impact of Fraud on Financial Assistance Programs and Its Prevention: A Case Study of Merankabandi, Burundi - Desire Ndayizeye; Kalgi Shah (European Scientific Journal, ESJ, 2026)
The purpose of this study is to examine the frequency and processes of fraud on financial assistance programs, with a focus on Merankabandi in Burundi. It aimed to identify systemic vulnerabilities and recommend evidence-based preventive strategies to enhance program integrity and effectiveness. The design, methodology, and approach in this research involve reviewing documents and published papers as secondary data, conducting household survey answers analysis, interviewing local administrators, and observing in the field to thoroughly examine Merankabandi’s governance model in comparison to similar programs worldwide, thereby providing a context for its challenges. Data collected from a population of 56.104 and a sample of 96 beneficiaries, the majority of whom are female (92%), have little education, and work predominantly on farms. The modest direct admission of fraud categories contrasts with a large understanding of systemic vulnerabilities such as insufficient aid, a lack of guide manuals, and, most notably, low digital literacy (96%). The discussions of the findings in this research suggest that there may be either a misunderstanding of fraud or that fraud is genuinely low and unappreciated in Merankabandi, Burundi. Importantly, the study stresses the link between fraud and socioeconomic vulnerability, such as households with less education and digital abilities are disproportionately exposed to systemic risks, decreasing program integrity and trust in aid delivery. The recommendations stress a context-specific strategy that incorporates community-driven monitoring, digital literacy training, and safe whistleblower practices. The ultimate goal is to increase integrity, lower the risk of fraud, and decrease the efficacy of financial aid in vulnerable environments.